Determining vehicle pre-crash speed in frontal barrier crashes using genetic algorithm model adjustment techniques for intermediate car class. Issue 4 (15th July 2022) - Mrowicki, Adam; Krukowski, Mateusz; Turoboś, Filip; Jaśkiewicz, Marek; Radkowski, Stanisław; Kubiak, Przemysław
Abstract: This paper introduces another approach to pre-crash velocity determination by the means of genetic algorithm model adjustment (GAMA). This innovative method is based on the standard genetic algorithm approach applied to the problem of determining the dependency of predicted variable on given parameters. The experiment is performed on a database obtained from NHTSA (National Highway Traffic Safety Administration), which contains potent number of data samples regarding frontal vehicle crash tests: i.e. vehicle mass, deformation zone and deformation coefficients C1-C6. Various classes of possible functions are considered and the model for determining the pre-crash speed based on the given parameters is obtained.